Shameless, the push-pull of transatlantic fiction format adaptation, and star casting. Issue 3 (3rd July 2018) - Knox, Simone
ABSTRACT: Fiction format adaptations have scored notable successes in recent years and been attracting increasing scholarly attention. The US version of Shameless has been one of the most conspicuous: based on Paul Abbott's series (C4 2004–2013), Shameless USA (2011-present) has become a signature series for Showtime. While Shameless USA has attracted a good amount of coverage in critics' and press discourses, it has, compared to its British progenitor, received scant mention in scholarship. This article provides a detailed examination of Shameless ' transatlantic move, because this offers the opportunity to capture the complex push-pull of textual and contextual factors that impede or facilitate fiction format adaption. The article traces the protracted development process for Shameless USA and considers the ways in which this format adaptation engages with issues concerning the politics of representation, especially in terms of the family and social class. Via a comparative analysis of the presence of actors David Threlfall and William H. Macy in their respective versions, the article furthermore pays attention to star casting. Drawing and building on the notion of 'contested cultural space', the article argues that star casting is crucial to, yet has thus far received insufficient attention in scholarship on fiction format adaptations.